2019
DOI: 10.1161/circulationaha.118.039177
|View full text |Cite
|
Sign up to set email alerts
|

Empagliflozin and the Risk of Heart Failure Hospitalization in Routine Clinical Care

Abstract: Background: The EMPA-REG OUTCOME trial showed that empagliflozin, a sodium-glucose co-transporter-2 inhibitor (SGLT2i), reduces the risk of hospitalization for heart failure (HHF) by 35%, on top of standard of care in patients with type 2 diabetes (T2D) and established CV disease (CVD). The EMPagliflozin compaRative effectIveness and SafEty (EMPRISE) study aims to assess empagliflozin's effectiveness, safety, and healthcare utilization in routine care from 08/2014 through 09/2019. In this first interim analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
188
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 175 publications
(215 citation statements)
references
References 25 publications
18
188
1
4
Order By: Relevance
“…The CV safety of SGLT‐2is has been assessed in randomized placebo‐controlled CVOTs of patients with T2D and established CVD or varying levels of CV risk, as well as in real‐world studies of patients who newly initiated SGLT‐2i therapy (CVD‐REAL, CVD‐REAL 2, EMPRISE and EASEL) . A 14% reduction in the risk of major adverse CV events (MACE) (CV death, MI or ischaemic stroke; primary safety end point) with SGLT‐2is compared with placebo was observed in the EMPA‐REG OUTCOME trial, in which more than 99% of patients had established CVD, and in the CANVAS trial in patients with established CVD (66%) or multiple CV risk factors (Table ) .…”
Section: Outcomes and Sglt‐2 Inhibitorsmentioning
confidence: 99%
See 4 more Smart Citations
“…The CV safety of SGLT‐2is has been assessed in randomized placebo‐controlled CVOTs of patients with T2D and established CVD or varying levels of CV risk, as well as in real‐world studies of patients who newly initiated SGLT‐2i therapy (CVD‐REAL, CVD‐REAL 2, EMPRISE and EASEL) . A 14% reduction in the risk of major adverse CV events (MACE) (CV death, MI or ischaemic stroke; primary safety end point) with SGLT‐2is compared with placebo was observed in the EMPA‐REG OUTCOME trial, in which more than 99% of patients had established CVD, and in the CANVAS trial in patients with established CVD (66%) or multiple CV risk factors (Table ) .…”
Section: Outcomes and Sglt‐2 Inhibitorsmentioning
confidence: 99%
“…Similarly, the EASEL study confirmed a significantly lower risk of the composite of all‐cause mortality or hospitalization for HF (43%) or the composite of all‐cause mortality, non‐fatal MI or non‐fatal stroke (33%) among US patients with established CVD at baseline . In an interim analysis of the real‐world EMPRISE study, US patients initiating empagliflozin therapy within routine care showed a 50% reduction in the risk of hospitalization for HF (primary diagnosis) compared with those using sitagliptin . A population‐based US cohort study also showed a 30%‐49% reduction in the risk of hospitalization for HF with canagliflozin compared with other glucose‐lowering drugs (dipeptidyl peptidase‐4 inhibitor [DPP‐4i], GLP‐1RA, or sulphonylurea therapy) …”
Section: Outcomes and Sglt‐2 Inhibitorsmentioning
confidence: 99%
See 3 more Smart Citations